Decay of light scalar mesons into vector-photon and into pseudoscalar mesons - Giacosa, Francesco; Pagliara, Giuseppe (Nuclear physics. A, Nuclear and hadronic physics, 2010)
The decays of a light scalar meson into a vector meson and a photon (S→Vγ) are evaluated in the tetraquark and quarkonium assignments of the scalar states. A link with the radiative decays ϕ→Sγ is established: experimental results for S→Vγ will make it possible to decide if the direct, quark-loop contribution to ϕ→Sγ or the kaon-loop contribution is dominant. Also strong decays S→PP - where P denotes a pseudoscalar meson - are investigated: within our scheme, the tetraquark assignment works better than the quarkonium one.